2016
DOI: 10.1111/clr.12897
|View full text |Cite
|
Sign up to set email alerts
|

Positive effect of strontium‐oxide layer on the osseointegration of moderately rough titanium surface in non‐osteoporotic rabbits

Abstract: The strontium-oxide layer on the SLA surface has the potential to improve implant osseointegration in non-osteoporotic rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 48 publications
4
31
0
Order By: Relevance
“…This was in accordance with the present experiment that showed that a significantly lower BIC% and BA% around the implants were found in osteoporotic bone compared with healthy bone. Regarding the effect of the Sr‐incorporated surface, it was found that the SLA‐Sr surface had the potential to improve bone‐to‐implant osseointegration in non‐osteoporotic models in our previous studies (Chen et al, ; Fan et al, ; Zhou et al, ), which was confirmed in the current study. Furthermore, SLA‐Sr implants displayed better effects on bone formation compared with SLA implants in osteoporotic animals, which was in accordance with other reports (Offermanns et al, ; Rohnke et al, ), indicating that Sr ions do have positive effects on promoting early osseointegration not only in healthy animals but also in osteoporotic animals.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This was in accordance with the present experiment that showed that a significantly lower BIC% and BA% around the implants were found in osteoporotic bone compared with healthy bone. Regarding the effect of the Sr‐incorporated surface, it was found that the SLA‐Sr surface had the potential to improve bone‐to‐implant osseointegration in non‐osteoporotic models in our previous studies (Chen et al, ; Fan et al, ; Zhou et al, ), which was confirmed in the current study. Furthermore, SLA‐Sr implants displayed better effects on bone formation compared with SLA implants in osteoporotic animals, which was in accordance with other reports (Offermanns et al, ; Rohnke et al, ), indicating that Sr ions do have positive effects on promoting early osseointegration not only in healthy animals but also in osteoporotic animals.…”
Section: Discussionsupporting
confidence: 86%
“…Immediately after specimen harvest, femur samples with implants were embedded in a quadrate metal box on an electronic torsion testing machine (CTT2500; MTS Company). This testing equipment measured the gradually increasing force value in Newton centimetres (Ncm) required to loosen the implant from the bone sample, as previously reported (Fan et al, ). The compression force was applied at a speed of 5°/min, and the peak removal torque force was recorded by a single‐blinded and experienced examiner.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…More recently, several experimental studies have shown promising results in terms of increased bone formation after Sr enrichment of various bone substitute materials, such as allogeneic bone [19], bioactive bioglass [20,21], calciumsilicon ceramic [22], calcium phosphate [23,24], and hydroxyapatite [25,26]. Furthermore, it was observed in recent experiments that Sr-loaded titanium implants presented significantly increased bone-to-implant contact, comparing to control implants [27][28][29]. Thus, another approach to enhance the bone regenerative potential of DBB may be to combine it with strontium (Sr).…”
Section: Introductionmentioning
confidence: 99%